Closing auctions: Nasdaq versus NYSE - Jegadeesh, Narasimhan; Wu, Yanbin (Journal of Financial Economics, 2022)
Closing auction volume steadily increased over the last decade, and it reached a peak of about 10% of the total trading volume in 2019. We examine the price impact and resiliency of closing auctions, and we compare closing auction liquidity in Nasdaq and the NYSE. The NYSE offers more depth. In both exchanges, it takes about 3–5 days for the temporary component of the price impact to fully dissipate. Trading strategies that exploit this price impact and its reversals are significantly profitable.